2019
DOI: 10.1093/jnci/djz105
|View full text |Cite|
|
Sign up to set email alerts
|

A Network Meta-Analysis of Surgical Treatment in Patients With Early Breast Cancer

Abstract: Background In early breast cancer treatment, the preferred surgical regimen remains a topic of controversy, and conventional pairwise meta-analysis cannot provide a hierarchy based on clinical trial evidence. Therefore, a network meta-analysis was performed both for direct and indirect comparisons and to assess the survival outcomes of surgical regimens. Methods Randomized clinical trials comparing different surgical regimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 99 publications
0
6
0
1
Order By: Relevance
“…Through prospective randomized trials, related studies have confirmed that BCS combined with SLNB in patients with lymph node-negative breast cancer has a better physical and psychological impact on patients than previous axillary lymph node dissection treatment, and lower occurrence rate of complications (17,18). In this study, the results showed that patients undergoing BCS combined with SLBN and axillary preservation treatment experienced significantly lower operation times, intraoperative blood loss, and extubation times than did the control group, with the quality of life after treatment being better than that of the control group; also, 93.42% of patients in the combined group gave a good or excellent rating for the postoperative cosmetic result, which as significantly higher than that given by the control group (P<0.05); no significant difference was found in the recurrence and metastasis rate compared with the control group, which was consistent with the results of previous studies (19).…”
Section: Discussionmentioning
confidence: 99%
“…Through prospective randomized trials, related studies have confirmed that BCS combined with SLNB in patients with lymph node-negative breast cancer has a better physical and psychological impact on patients than previous axillary lymph node dissection treatment, and lower occurrence rate of complications (17,18). In this study, the results showed that patients undergoing BCS combined with SLBN and axillary preservation treatment experienced significantly lower operation times, intraoperative blood loss, and extubation times than did the control group, with the quality of life after treatment being better than that of the control group; also, 93.42% of patients in the combined group gave a good or excellent rating for the postoperative cosmetic result, which as significantly higher than that given by the control group (P<0.05); no significant difference was found in the recurrence and metastasis rate compared with the control group, which was consistent with the results of previous studies (19).…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is the treatment option for most breast cancer patients. Precise surgical margin determination is still a clinical problem 114,125 . MPM provides a new idea for determining the surgical margin through observing the TME.…”
Section: Monitoring Breast Cancer Therapy By Mpmmentioning
confidence: 99%
“…1 Conventional treatment modalities encompass surgical resection, radiotherapy, and chemotherapy, yet they are prone to triggering relapse and metastasis. [2][3][4] In recent years, photothermal therapy (PTT) has garnered significant attention owing to its virtues of minimal invasiveness, high precision, and minimal harm to healthy tissues. [5][6][7][8][9] During laser irradiation, photothermal agents (PTAs) effectively convert near-infrared (NIR) laser energy into localized heat, resulting in swift tumor ablation.…”
Section: Introductionmentioning
confidence: 99%